Bioprinting in Regenerative Medicine - Turksen, Kursad (Stem Cell Biology and Regenerative Medicine,, 2015)
This volume explores laser-assisted bioprinting, focusing on the most recent developments in its use for  tissue engineering. Bringing together authoritative and international perspectives, the text begins with an overview and goes on to cover bioprinting in cell viability and pattern viability, tissue microfabrication to study cell proliferation, microenvironment for controlling stem cell fate, cell differentiation, zigzag cellular tubes, cartilage tissue engineering, osteogenesis, vessel substitutes, skin tissue and much more. Bioprinting is on its way to becoming a dominant technology in tissue-engineering; Bioprinting in Regenerative Medicine, from the bestselling Stem Cell Biology in Regenerative Medicine series, is essential reading for those researching or working in regenerative medicine, tissue engineering, or translational research. Those studying or working with stem cells who are interested in the development of the field will also find the information invaluable.